Tren Penelitian Keterampilan Berpikir Kreatif dalam Jurnal Pendidikan Biologi di Indonesia - Syamsurizal; Yogi Valfa; Lufri (Postgraduate, University of Mataram, 2023)
This research aims to conduct content analysis of various articles about creative thinking skills in Indonesian biology education journals. This research method is content analysis using the document scanning method which is used as a research method. In this research, the articles analyzed were downloaded from the Journal of Biology Education in Indonesia website. This study adheres to the principle of content analysis, which focuses on findings from various studies published in scientific journals in Indonesia. The results of this study reveal that in the last 5 years, the number of publications regarding creative thinking skills has increased. Among all the research obtained, quantitative research was the most dominant. Furthermore, class X high school students and environmental pollution materials are the subjects and materials most researched. The problem-based learning model is the treatment most often used as a treatment in looking at creative thinking skills. Test instruments and t-tests are the most commonly used instruments and data analysis methods. From the results of this study, it can be concluded that research on creative thinking skills in biology journals in Indonesia has increased.